Absorção, assimilação e transporte de nitrogênio em plantas de Physalis angulata L. - Tanan, Tamara Torres (2019)
Brazil stands out for its vegetal biodiversity; however, several species are underutilized despite great potential,this is the case of Physalis angulata L. The biological activity of this species isextensively investigated; but little information is available on its cultivation and physiological aspects. The aim of this study was to describe the influence of the use of different nitrogen sources on growth, metabolism and fruit quality in P. angulata plants, as well as to adapt protocols for quantification of chlorophyll and nitrate reductase enzyme activity (RN) in plant tissue of the species. We evaluated the use of 80% acetone, 95% ethanol and dimethyl sulfoxidefor the extraction of chlorophyll. Of these, the traditional technique of maceration of the vegetal tissue with 80% acetone was more efficient, however, because it does not differ and because of the ease of obtaining, handling and lower cost of this solvent, we suggest the use of 95% ethanol. The reduction of nitrate occurs in both root and leaves, with higher activity during periods of higher solar radiation and temperature. Based on variations in the conditions of the in vivo method for quantification of NR activity, we recommend for P. angulata the use of 1% n-propanol and 50 mM KNO3- addition in the incubation medium with pH 7 of phosphate buffer, which must be incubated in a water bath for 75 minutes to determine maximum activity. For the analysis of the effect of different nitrogen sources, we used five proportions of NO3-:NH4+ (100: 0, 75:25, 50:50, 25:75 and 0: 100) in the hydroponic nutrient solution. The ammonium levels reduced stem and root length, number of branches, leaf expansion, and chlorophyll content, as well as delaying flowering and fruiting, and altering the main site of NR activity. However, the application of NO3- and NH4+ together alleviated toxicity symptoms, with the ratios of 75:25 and 50:50 NO3-: NH4+ giving better development and growth. The use of 50:50 of NO3-:NH4+ is advisable because it produces larger fruits, more sweet and with vigorous seeds. The N-form used affected the metabolism of carbon, with reduction in stomatal conductance, transpiration, and accumulation of sugars and amino acids when supplied with NH4+. The availability of both ionic forms promotes higher concentration of N-total, and leads to the equilibrium of charges, avoiding the reduction of other cations and anions.